Hubungan Komunikasi Orang Tua pada Kesejahteraan Mental Mahasiswa - Andini Sulistiawati; Naylla Aisy Khalesya; Sri Mulyeni (Pusat Riset dan Inovasi Nasional, 2026)
Students’ mental well-being is an essential aspect in supporting academic success and psychological development during emerging adulthood. Good mental well-being enables students to manage stress effectively, maintain emotional stability, and adapt positively to academic and social demands. One of the factors that influences students’ mental well-being is the quality of parental communication and support. Open, empathetic, and supportive communication can serve as an important source of emotional support for students in dealing with various pressures during their academic life. This study aims to examine the relationship between parental communication and students’ mental well-being. A quantitative approach with a correlational design was applied using a survey method. The participants consisted of 59 active students from the Psychology Department of Pasim National College, all of whom were included through a census sampling technique. Data were collected using Likert-scale questionnaires that had met validity and reliability criteria. Correlational analysis was conducted to identify the relationship between parental communication and students’ mental well-being. The findings indicate a significant relationship between the two variables. Students who experience positive parental communication tend to demonstrate better mental well-being, as reflected in effective stress management, emotional stability, and resilience in coping with academic pressures. In contrast, high parental expectations that are not accompanied by effective and supportive communication may increase psychological stress. These findings highlight the importance of parental communication and emotional support within the family as key factors in promoting students’ mental well-being.